Duvelisib for the treatment of chronic lymphocytic leukemia. (23rd July 2020) - Frustaci, Anna Maria; Tedeschi, Alessandra; Deodato, Marina; Zamprogna, Giulia; Cairoli, Roberto; Montillo, Marco
ABSTRACT: Introduction: Duvelisib, a first in class, oral, dual PI3 k-delta/gamma inhibitor recently received FDA approval for previously treated CLL (chronic lymphocytic leukemia)/SLL (small lymphocytic lymphoma) and follicular lymphoma. Data coming from the phase III 'DUO' trial, in fact, showed a superior progression-free survival (PFS) in CLL patients treated with duvelisib compared to ofatumumab Areas covered: This review provides analysis of the mechanism of action of duvelisib and includes the rationale for the use of double inhibition. The authors also give their clinical experience with duvelisib. Overall, despite the high efficacy of the drug, some concern remains on duvelisib-related adverse events leading to treatment interruption in a significant proportion of patients. Expert opinion: Considering the unmet need of salvage therapies in patients failing BTK and/or Bcl2 inhibitors, treatment with duvelisib represents a new valid option in the CLL therapeutic armamentarium. Therefore, the correct management of adverse events with early treatment suspension, dose reductions and prompt supportive treatment could help to manage treatment, thus improving patient outcome. Finally, the association of duvelisib with other targeted therapies, such as ibrutinib or venetoclax, could allow clinicians to capitalize on the synergistic activity of these agents.